Personality correlates of stutterers. - Y.T. Balakrishna Acharya (Journal of All India Institute of Speech and Hearing, 1970)
We live in a world of communication. Speech is essentially the basic mode of communication through which we interact with others in our day to day life. It is one unique ability that distinguishes the human from the rest of the species. Communication becomes more effective when we speak naturally, fluently and clearly without any interruptions.